The Influence of the Use of Social Media on the Intensity of Worshipping the Millenial Generation using Linear Regression - Fakhri Faisal Rochdiana; Muhammad Rizki Isa Darmawan; Nurul Aulia Dewi; Wafda Zulfa Husna; Zulfa Dwi Audina; Nunik Destria Arianti (Asosiasi Khazanah Cendekia, 2023)
Worship is an activity carried out by every religious community. Sometimes there are activities that can interfere with worship activities, especially in the current era of globalization. In the current era of globalization, many people use their smartphones or gadgets for their daily needs. The millennial generation is one of the generations that has begun to be introduced to this gadget or smartphone, so that many of these millennial generations cannot be separated from what is called social media. During the COVID-19 pandemic, almost all our daily time is used to view social media. The purpose of this study was to see the effect of using social media on the intensity of worship of the millennial generation. The method used to assist this research is to use linear regression. The result of this research shows that the use of gadgets for a long time is accompanied by an extraordinary intensity of worship. This research also concludes that there is no influence given using social media on the intensity of worship of the millennial generation.